Early Greek Epic Fragments I. - Tsagalis, Christos (Trends in classics. Supplementary volumes, 2017)
This is the first full-scale commentary on the extant fragments of genealogical and antiquarian epic of the archaic period since G. Marckscheffel?s Latin commentary in 1840. It includes introduction to the relevant authors and poems, Greek text, translation, detailed commentary, index of the sources transmitting these texts, and a 'comparatio numerorum' with all the previous major editions.